Analysis of geotechnical problems using hardening soil model - Tan, Chun Yih. (2009)
Plaxis is becoming an increasingly popular tool for solving complex geotechnical problems. While it is a powerful tool intended for the two dimensional analysis of deformation and stability in geotechnical engineering, users need to be properly trained to develop the necessary skills for running and obtaining meaningful results when using the program.